PROYEKSI KEBUTUHAN DAYA LISTRIK DI PROPINSI SULAWESI TENGAH TAHUN 2007-2020 - Hamdany, Tadjuddin (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
The study is devoted to forecast electrical energy demand from 2007 to 2020, so lack of energy can be anticipated. The study was conducted in Palu, province of Central Sulawesi. The data is analyzed using linear regression. The result showed that the increasing of load in 2007 is very significant with peak load reached 120,6 MW. In 2020 the peak load reached 196.2 MW. Keywords : electrical energy, load growth, and load forcecasting.